Pelatihan Membuat Toko Online Menggunakan Wordpress Di Kelurahan Jatisampurna - Imam Yunianto; Muhamad Malik Mutoffar; Sri Kuswayati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The classic problem for city residents is the economic problem which is still not evenly distributed, where there are already residents with a high economic level, but there are still many city residents whose economy is below the poverty line due to low education and minimal skills so they can only work as unskilled laborers. minimal income. For this reason, this article wants to propose skills training that can be used to improve the economy by becoming an entrepreneur who uses websites to market his wares. With training to create an online shop using WordPress, the costs required by residents are not expensive and the material taught is also not too difficult. Hopefully this training can be a solution to the problems of city residents.